“Are we architects or construction workers?” Re-examining teacher autonomy and turnover in charter schools - Torres, A. Chris (Education Policy Analysis Archives, 2014)
Charter school teachers nationwide expressed greater autonomy compared to traditional public school teachers at the turn of the century. But is this trend changing? The recent proliferation of Charter Management Organizations (CMOs), which often have prescriptive organizational models, has raised questions around how teachers perceive autonomy and control in these schools. Researchers consistently find that faculty input into decision-making has a strong influence on staff commitment and turnover. This exploratory, interview-based study critically examines why and how CMO teacher autonomy is linked to turnover. CMO teachers linked various concerns over autonomy, which was limited by their organization’s model, with decisions to leave their jobs. Teachers with strong expectations for autonomy or ideas inconsistent with their school’s model experienced substantial conflict involving the discipline or socialization of students that affected their career decisions. Teachers’ desires to have a voice in issues surrounding students’ socialization ultimately hinged upon their skepticism that current practices were adequately preparing students for college and life.